2015
DOI: 10.1007/s00246-015-1261-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Ultrasound Cardiac Output Monitor as a Bedside Tool for Pediatric Patients

Abstract: The aim of our study was to determine the validity of cardiac output (CO) measurements taken with the ultrasonic cardiac output monitor (USCOM) by comparing to CO measured by pulmonary arterial catheter (PAC) thermodilution during cardiac catheterization. We enrolled thirty-one children (<18 years) undergoing cardiac catheterization in this double-blinded, prospective, observational study. The median CO measured by USCOM was 4.37 L/min (IQR 3.73, 5.60 L/min) compared to 4.28 L/min (IQR 3.52, 5.26 L/min) by PAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…9 Previous studies have validated the accuracy of this method and have shown that it is highly accurate against other standard hemodynamic assessment techniques; this technique has also been applied in many clinical applications with critical patients. 7 , 8 , 10 This noninvasive method is the most reasonable test for runners in both a pre- and postrace assessment setting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Previous studies have validated the accuracy of this method and have shown that it is highly accurate against other standard hemodynamic assessment techniques; this technique has also been applied in many clinical applications with critical patients. 7 , 8 , 10 This noninvasive method is the most reasonable test for runners in both a pre- and postrace assessment setting.…”
Section: Methodsmentioning
confidence: 99%
“…The noninvasive ultrasonic flow measurement (USCOM; Sydney, Australia) is an advanced hemodynamic assessment method with reliable accuracy when compared to other standard methods and has been validated by many previous publications. 7 10 This is a noninvasive assessment which will not impair the performance of the runners before and after the race. This study was conducted to identify race predictors which could predict the race results and classify the runners allowing better safety management during the race and also to evaluate the physiologic effects of prolonged endurance physical exercise with a noninvasive flow assessment method.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a fluid responsiveness‐based resuscitative strategy for sepsis has recently been described in adults and awaits study in larger trials. The validation of several non‐invasive cardiac output monitors in children may pave the way for similar trials in a younger age group …”
Section: Fluid Volumementioning
confidence: 99%
“…Concerning young patients, some authors claim children tend to have reliable USCOM measurements, as long as they are not critically ill or suffer from a structural heart disease [67,69]. A third study confirms this statement, yet reports a percentage error of 58% compared to TTE [70].…”
Section: Ultrasonic Cardiac Output Monitoringmentioning
confidence: 96%